Garstang Stela E.31 and the Family of Iy at Abydos - Davies, Huw P. R. Twiston (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
Publication of E.31, a Middle Kingdom stela from cenotaph 321 A’07, discovered by John Garstang at Abydos, currently housed in the Garstang Museum of Archaeology, University of Liverpool. The stela contains information about the family of the Bearer of Soil Iy at Abydos in the late Middle Kingdom, adding to Simpson’s ANOC 19. The archaeological context of the object is explored, and a full translation of E.31 is provided, as well as discussion of a heavily fragmented stela (321d) found in the same context by Garstang.